Optimizing the Production of Glass Ceramic from East Lampung Basalt Rock Using Taguchi and ANOVA Analysis Methods - Syaipudin Anwar; Irza Sukmana; Zulhanif Zulhanif; Rizal Adi Saputra; Tarkono Tarkono; A Yudi Eka Risano (TURBO [Tulisan Riset Berbasis Online], 2025)
Glass-ceramics are fine-grained polycrystalline materials produced by controlled crystallization in the glass phase. The raw material for glass ceramics is basalt rock from East Lampung mixed with additives (SiO₂, MgO, and CaO). The production of glass ceramics begins with melting at 1200 °C for 2 hours until melting. The melted basalt is quenched using aquadest water with a pH of 7 to produce glass material. The glass material is ground using a ceramic ball mill and sieved with a 325 mesh. The glass material undergoes nucleation at 600 °C for 2 hours, followed by crystallization at 1,050 °C for 3 hours, and thermal crystallization (devitrification) at 1,050 °C for 3 hours to form the crystalline phase. The additive composition was varied using the Taguchi method to analyze its effect on density. The density test results showed values ranging from 2.1 to 3.8 g/cm³, depending on the additive ratio used. An increase in CaO and MgO content tends to increase density due to the formation of crystalline phases such as pyroxene, anorthite, and olivine. Conversely, excessive addition of SiO₂ can reduce density due to the growth of amorphous phases. Taguchi analysis identified Silica (SiO2) as the Rank 1 parameter influencing density. Meanwhile, ANOVA analysis yielded an optimal percentage contribution of silica at 34.57%.